Environmental impacts of genetic improvement of growth rate and feed conversion ratio in fish farming under rearing density and nitrogen output limitations. (10th March 2016) - Besson, M.; Aubin, J.; Komen, H.; Poelman, M.; Quillet, E.; Vandeputte, M.; van Arendonk, J.A.M.; de Boer, I.J.M.
Abstract: Today, fish farming faces an increasing demand in fish products, but also various environmental challenges. Genetic improvement in growth rate and feed conversion ratio is known to be an efficient way to increase production and increase efficiency in fish farming. The environmental consequences of genetic improvement in growth rate and feed conversion ratio, however, are unknown. In this study, we investigated the environmental consequences of genetic improvement in growth rate and feed conversion ratio in an African catfish farm, using Recirculating Aquaculture System (RAS). In RAS, total fish production of the farm is limited by rearing density or by the capacity to treat dissolved nitrogen. To evaluate the environmental consequences of genetic improvement in growth rate and feed conversion ratio, we combined life cycle assessment and bioeconomic modelling of genetic response to selection. We explored different impact categories, such as climate change, eutrophication, acidification and energy use, and we expressed impacts per ton of fish produced. Results show that the environmental impact of genetic improvement in growth rate and feed conversion ratio varies among impact categories and depends on the factor limiting production at farm level (i.e. rearing density or nitrogen treatment capacity). Genetic improvement of feed conversion ratio reduces environmental impacts in each scenario tested, while improving growth rate reduces environmental impacts only when rearing density limits farm production. Environmental responses to genetic selection were generally positive and show similar trends as previously determined economic responses to genetic improvement in growth rate and feed conversion ratio in RAS. These results suggest that genetic improvement of growth rate and feed conversion ratio for species kept in RAS will benefit both the environmental impacts and the economics of the production system. Highlights: We combined a bioeconomic model and a life cycle assessment. We estimated the environmental impacts of genetic improvement in fish farming. Improving growth keeps environmental impacts constant in nitrogen limiting condition. Improving feed conversion ratio always decreases environmental impacts. We observed that decreasing environmental impacts could increase farm profitability.